Efficacy and safety of risankizumab versus methotrexate in patients with moderate-to-severe plaque psoriasis: results from IMMbrace, a randomized, double-blind, phase 3 study with an open-label extension period in Brazil - Cestari, Tania F.; Souza, Cacilda da Silva; Azulay-Abulafia, Luna; Romiti, Ricardo; Carvalho, André V.E.; Silva de Castro, Caio César; Marques, Sílvio Alencar [UNESP]; Antonio, João Roberto; Fabrício, Lincoln; Soliman, Ahmed M.; Wu, Tianshuang; Sinvhal, Ranjeeta; et al. (Elsevier, 2025)
Background: Psoriasis, a chronic, inflammatory skin disease, requires long-term therapy. Risankizumab is a humanized immunoglobulin G1 monoclonal antibody that specifically inhibits interleukin 23 by binding to its p19 subunit. Objective: The authors assessed the efficacy and safety of risankizumab compared with methotrexate in adults with moderate-to-severe plaque psoriasis. Methods: IMMbrace was a phase 3, multicenter, randomized, double-blind, double-dummy, active-controlled study. Patients received subcutaneous risankizumab 150 mg at weeks 0, 4, and 16 plus oral placebo weekly, or oral methotrexate 5 mg weekly (with dose escalation up to 25 mg based on response and tolerability) plus subcutaneous placebo at weeks 0, 4, and 16. Primary efficacy endpoints were the proportions of patients who achieved ≥ 90% improvement in Psoriasis Area and Severity Index (PASI90) and static Physician's Global Assessment of clear/almost clear (sPGA 0/1) at week 28. Safety was also assessed. Results: Among 98 patients randomized (risankizumab, n = 50; methotrexate, n = 48), 95 completed the double-blind period. At week 28, significantly higher proportions of patients treated with risankizumab versus methotrexate achieved PASI90 (84.0% vs. 35.4%; p < 0.001); sPGA 0/1 was achieved by 90.0% and 64.6% of patients in the risankizumab and methotrexate groups (p ≤ 0.001). Risankizumab efficacy was maintained throughout week 112. Adverse event rates were similar in the two groups. Study limitations: The sample size was small due to the difficulty of recruiting patients without methotrexate use. Conclusions: Risankizumab demonstrated superior efficacy over methotrexate at week 28; efficacy was maintained, and no new safety findings were observed through week 112.
Keywords: Methotrexate; Psoriasis; Risankizumab